Analysis of surface temperature measurements over complex urban sites - Dezső, Zsuzsanna; Pongrácz, Rita; Bartholy, Judit (Geographica Pannonica, 2019)
The aim of this study is to analyse the thermal properties of natural and artificial urban surfaces and the impact of surface colours and shading. Measuring campaigns were conducted in spring and summer (2018–2019) in the district XI of Budapest to determine the surface temperature of various urban materials. The results show that the coolest surfaces are natural covers (water, vegetation), while the hottest surfaces are concrete pavements, asphalt and rubber paving when exposed to direct solar radiation. Moreover, among concrete pavements, light coloured surfaces warm up 5-6 °C less on average compared to dark coloured surfaces. The use of rubber paving may be disadvantageous from the urban climatological point of view, as these surfaces become extremely hot under sunny conditions.
Keywords: surface temperature measurements; concrete pavements; rubber paving; outdoor thermal comfort; Budapest